Peningkatan Induksi Kalus Embriogenik dan Konversi Embrio Somatik Kopi Robusta Klon BP 308 - Meynarti Sari Dewi Ibrahim; RR. Sri Hartati (Jurnal Tanaman Industri dan Penyegar, 2017)
Robusta coffee (Coffea canephora) is a cross-pollinated plant, therefore vegetative propagation is necessary to ensure identical traits with parents, such as tissue culture techniques through somatic embryo. The study aimed to find the effect of plant growth regulator 2.4-D and thidiazuron in inducing embryogenic callus, by adding incision area on leaf explant, and to evaluate addition of GA3 in increasing somatic embryo conversion. The study was conducted from December 2014 to June 2016 in the Tissue Culture Laboratory, IAARD, Bogor. The research consisted of 2 stages. Stage 1 used a complete randomized design of 2 factors; the first factor was a combination of plant growth regulator 2.4-D (1.0 and 2.0 mg/l) and thidiazuron (1.0; 3.0; and 5.0 mg/l), the second factor was leaf incision (slashed and unslashed). Stage 2 used a complete randomized design, with GA3 treatment at different concentrations (0.0; 0.5; and 1.0 mg/l). Observed variables were percentage of callus formation, fresh weight of callus, number of torpedoes, number of somatic embryos at cotyledon stage, and number of germinated embryo. The results showed growth regulatory treatments influenced the percentage of embryogenic callus formation and fresh weight of callus. Extra incision on leaf showed no effect in  embryogenic callus induction. Embryogenic callus inducted using 2.4-D 1.0 mg/l + thidiazuron 5.0 mg/l medium which  then regenerated in ½ MS medium added with kinetin 2 mg/l exhibited  the highest number of germination.  Adding GA3 1.0 mg/l in regeneration medium is recommended to increase somatic embryos of Robusta coffee BP 308 clone.